Utilization of QR Code Technology in Population Management and Identification of Cattle in Sindue District, Central Sulawesi - Yudi Mujayin; Hauris Hauris; Fitrah Fakhirah; Alda Pratiwi (Biology, Medicine, & Natural Product Chemistry, 2025)
The implementation of a QR barcode-based recording system in Sindue District aimed to improve livestock management efficiency. However, digital transformation in rural livestock management faces challenges such as a lack of technological understanding and limited smartphone access. The objective of this study was to analyze livestock farmers' perceptions of the recording system and digital transformation. The method used in this study was a survey with structured interviews (questionnaires) with 66 sample livestock farmers. Data analysis used descriptive statistics and correlation. The results showed that farmers' perceptions of QR barcode technology fell into the "Quite Agree" category, with a total score of 398. The knowledge subvariable showed limited understanding of QR barcode technology (63.8% did not understand), but awareness of its benefits received a high response (83.3% agreed). The socio-cultural aspect received a very positive response (score 195), while the constraints subvariable received a low response (score 106). Farmers support the implementation of a digital QR barcode recording system, although implementation remains hampered by limited technical understanding. Furthermore, correlation analysis shows a significant relationship between the recording system and digital technology (p < 0.05), with the strongest relationship being between sociocultural aspects and constraints (r = 0.750).